A world lit only by fire the medieval mind and the Renaissance ; portrait of an age - Manchester, William 1922-2004 (Little, Brown, 1992)
Explores the sordidness and the splendor of the Middle Ages as well as the collapse of the medieval mind and its metamorphosis into The Renaissance.
Keywords: Geschichte 1400-1520; Geestesgeschiedenis; Renaissance; Geschichte; Learning and scholarship -- History -- Medieval, 500-1500; Mittelalter; Kultur; Europa